Inhibiting efflorescence formation on fly ash–based geopolymer via silane surface modification. (November 2018) - Xue, Xiao; Liu, Yun-Lin; Dai, Jian-Guo; Poon, Chi-Sun; Zhang, Wei-Dong; Zhang, Peng
Abstract: Efflorescence can be a critical issue for the application of alkali-activated fly ash–based geopolymer products, especially when the products are in a moist environment. In this study, a new method was explored to inhibit efflorescence of fly ash–based geopolymer via silane surface modifications. After the modification, the surface of the geopolymer was transformed from hydrophilic to hydrophobic, with a water contact angle of 144.1°, and the capillary absorption and diffusion of water were significantly suppressed; and as a consequence, the soluble alkali ion leaching was reduced. Analysis by Fourier-transform infrared spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction, and size-exclusion chromatography demonstrated that the selected silane is attached successfully onto the surface of the fly ash–based geopolymer via chemical bonding instead of via physical absorption. A possible reaction mechanism for the silane surface modification of the fly ash–based geopolymer is proposed.